Effects of magnesium-aluminum hydroxide antacid on absorption of rufloxacin. - Lazzaroni, M (1993)
The present study was designed to determine the effects of an antacid suspension containing magnesium hydroxide and aluminum hydroxide (30 ml of Maalox) on the oral bioavailability of rufloxacin (400 mg). Rufloxacin was administered orally to 12 healthy volunteers according to a randomized, balanced, crossover design. Three treatments were administered to each subject, with a 10-day washout period between treatments; the treatments included rufloxacin alone, rufloxacin taken 5 min after antacid, and rufloxacin taken 4 h before antacid. Administration of antacid within 5 min before the administration of rufloxacin resulted in a substantial decrease in rufloxacin absorption, with a mean percent relative bioavailability compared with control values of 64% (range, 42 to 77%). Administration of antacid 4 h after the administration of rufloxacin slightly affected the absorption of the quinolone (mean relative bioavailability, 87%; range, 51 to 110%). Antacids that contain magnesium and aluminum salts reduce the absorption of rufloxacin. The extent of this interaction depends on the time that elapses between administration of the two drugs.